Estimation of crystallite size, density, and compositional of the Ti: Al2O3 single crystal - Kusuma, Hamdan Hadi; Ibrahim, Zuhairi; Othaman, Zulkafli (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
The purposes of this research were to estimate the crystallite size, density, and chemical composition of the ingot Ti: Al2O3  crystal grown by the Czochralski method. The crystallite size and composition of Ti: Al2O3 crystals had been determined using x-ray diffraction (XRD) and energy-dispersive x-ray spectroscopy (EDXS). Based on the Archimedes principle, the density of the crystals had been determined. The XRD patterns showed a single central peak with high intensity for all samples. It indicated that all samples had a single crystal. The average value of the samples' crystallite size was in the range of 20.798 nm to 34.294 nm. The ingot crystal density and Ti composition increased from the top to the bottom part because the solid solution was distributed unevenly during the growth process.